Association between psychosocial functioning, health status and healthcare access of asylum seekers and refugee children: a population-based cross-sectional study in a German federal state - Costa, Diogo; Biddle, Louise; Bozorgmehr, Kayvan (Child and adolescent psychiatry and mental health, 2021)
The mental health condition and healthcare needs of asylum seeking and refugee (ASR) children may go unrecognized if barriers to healthcare access exist accompanied by exclusive focus on somatic illness. We analysed the relationship between psychosocial functioning, health status and healthcare access of ASR children.